REGIONAL ASPECTS OF DEVELOPMENT AND MODERNIZATION OF THE TEXTILE INDUSTRY OF UKRAINE (Regional aspects of productive forces development of Ukraine, 2019)
The article states that one of the leading branches of the economy, which largely ensures the formation of the state budget and is an important factor in the development of other sectors, such as agriculture and the chemical industry, is light industry, including textiles. However, in Ukraine, these spheres of activity have been in a crisis for many years. The question arises as to finding out the reasons that prevent the outbreak of the crisis and justify the directions of further development of the textile industry.